2006
DOI: 10.1080/02724980443000863
|View full text |Cite
|
Sign up to set email alerts
|

Inference-driven attention in symbolic and perceptual tasks: Biases toward expected and unexpected inputs

Abstract: The aims of this paper are (a) to gather support for the hypothesis that some basic mechanisms of attentional deployment (i.e., its high efficiency in dealing with expected and unexpected inputs) meet the requirements of the inferential system and have possibly evolved to support its functioning, and (b) to show that these orienting mechanisms function in very similar ways in two perceptual tasks and in a symbolic task. The general hypothesis and its predictions are sketched in the Introduction, after a discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 82 publications
(83 reference statements)
5
11
0
Order By: Relevance
“…These patterns of attentional deployment work similarly for some perceptual tasks (tracking of perceptual trajectories) and for a symbolic task (tracking of simple arithmetic series). The behavioural results of the present experiments consistently replicate the findings of Cherubini et al (2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These patterns of attentional deployment work similarly for some perceptual tasks (tracking of perceptual trajectories) and for a symbolic task (tracking of simple arithmetic series). The behavioural results of the present experiments consistently replicate the findings of Cherubini et al (2006).…”
Section: Discussionsupporting
confidence: 92%
“…Behavioural findings replicate previous results by Cherubini et al (2006). As in Experiment 1, ERPs at S n corroborate the pattern of allocation of attention predicted by the inference-driven view of attentional deployment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study we use various mimicked "Posner" tasks in the propositional reasoning domain to corroborate the hypothesis that some attentional mechanisms are qualitatively similar in reasoning and perception. The results will be of interest both for the psychology of attention and the psychology of reasoning: first, by further corroborating the conjecture that the functional aspects of some orienting mechanisms may be of general importance and pervasive to the cognitive system, because they can be detected in visual orienting and in the orienting to symbolic spaces (Cherubini et al, 2006); second, by allowing the inferring of some general properties of the mental representations involved in deductive propositional reasoning.…”
Section: An Analogy With a Propositional Reasoning Tasksupporting
confidence: 53%
“…In other words, we hypothesize that the orienting of attention upon symbolic representations that support reasoning follows some principles similar to some mechanisms involved in the orienting of attention in visual space. The conjecture of a link between visual orienting and the orienting of attention in other domains has been put forward in very general terms by various authors in the attention literature, recently and less recently (e.g., Posner, 1980;Wolfe, 2003); however, to our knowledge the only study that empirically investigated the topic is Cherubini, Burigo, and Bricolo (2006). The authors found a common pattern of focusing attention on anticipated events and defocusing and redistributing attention after an unexpected event (i.e., the surprise effect) in two visual tracking tasks and in a task that required mentally tracking an arithmetic series.…”
mentioning
confidence: 99%